Studi Pendahuluan Analisis Kemampuan Berpikir Kritis Matematika Siswa Kelas VII SMP Negeri 1 Sukadiri - Mawar, Uning Duwi; Hartani, Mukti; Nurhasanah, Neneng (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2025)
The purpose of this preliminary study is to analyze the mathematical critical thinking abilities of seventh-grade students at SMP Negeri 1 Sukadiri. This study uses descriptive qualitative research. The analysis techniques used are interviews, observation, and documentation. The subjects in this preliminary study are mathematics teachers and seventh-grade students at SMP Negeri 1 Sukadiri. The results of the observation show that mathematics learning at SMP Negeri 1 Sukadiri is student-centered, where students tend to be active but hesitant in answering questions given by the teacher. The results of the interviews indicate that students struggle to understand and solve problems related to the material and basic concepts they have not mastered, which is compounded by a lack of HOTS practice questions and low interest in learning. The results of documentation show that students' test scores on statistics material are below the KKTP and have the lowest average score compared to other materials in the second semester. . Additionally, students in class VII.7 have the lowest average score among other seventh-grade classes on this material. The conclusion of this preliminary study is that students' mathematical critical thinking skills on statistics material do not meet expectations.